Assessing Self-Efficacy in Infant Care: A Comparison of Two Scales - Tassanee Prasopkittikun, RN, PhD; Narumon Vipuro, RN, MNS (Elsevier, 2008)
The Self-efficacy in Infant Care Scale (SICS) was developed with acceptable psychometric properties to assess the degree of Thai mothers' belief in their ability to perform designated infant care tasks. The purpose of this study was to identify whether the SICS, with a 6-point rating scale, can be used as an alternative to a rating scale with 0-100 confidence continuum scale. Methods: Eligible subjects included 42 mothers with 6 or 9 years of education who took their infants to the well-baby clinic for immunizations at Samutsakorn Hospital. Each mother first completed the original scale and then the 6-point SICS rating scale. Afterwards, the mothers were asked to indicate which of the questionnaires was easier to administer. Results: Using Cronbach's α, the reliability of both scales was .95. Correlations between the same items of both response formats of the SICS revealed that only 11 pairs of items demonstrated high magnitudes of correlation. Correlations between the same subscales and between the total scales of both response formats were high but less than .95. Slightly over half of all mothers (57%) preferred the 6-point rating scale. Interestingly, 59% of the group with 6 years of education preferred the original scale, compared with only 25% of the group with 9 years of education. Conclusion: The findings suggest that correlations between SICS and two different response formats do not reach the criteria for use as alternatives to each other. However, further research is needed, with particular emphasis on the investigation of construct validity and comparisons between the two scales.